AIDS : rights, risk, and reason - Aggleton, Peter; Davies, Peter (Peter M.); Hart, Graham, 1957- (Social aspects of AIDS., 1992)
First published in 1992. Routledge is an imprint of Taylor & Francis, an informa company.